Purple Sweet Potato Yogurt Affects Lipid Metabolism and Reduces Systemic Inflammation and Oxidative Stress in High Fat Diet Mice - Astrid Feinisa Khairani; Nur Atik; Putri Halleyana Adrikni Rahman; Enny Rohmawaty; Cynthia Noviyanti; Resti Santika; Jose Arimathea; Widad Aghnia Shalannandia (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Purple  sweet  potato  yogurt (PSPY) is a funtional food which is rich in anthocyanin and probiotics. However, the currently available data on its potentially protective effect on anthropometry, lipid metabolism, oxidative stress, and pro-inflammatory markers is very minimal, especially in mice. This study was performed to investigate those effects on balb/c mice models (Mus musculus) given a high-fat diet (HFD).METHOD: Balb/c mice were treated with or without standard diet, HFD, ethanol extract, yogurt, and PSPY according to the group. The changes of anthropometry were analyzed using Lee Index. After three months, the interscapular brown adipose tissue (iBAT) was morphologically observed with hematoxylin and eosin (H&E) staining. The blood serum was used for evaluation using cholesterol oxidase-peroxidase aminoantypirin (CHOD-PAP) for lipid profile, enzyme-linked immunoassay (ELISA) for tumor necrosis factor (TNF)-α and interleukin (IL)-6, and thiobarbituric acid reactive substance (TBARS) procedure for malondialdehyde (MDA).RESULT: Lee Index revealed a decrease in time (p<0.0001). The PSPY group showed a decrease in iBAT weight (p<0.05), lipid profiles including LDL (p<0.05) and total cholesterol (p>0.05), TNF-α and IL-6 (p>0.05), and MDA (p>0.05). Adipocytes’ density showed a significant increase (p=0.001). CONCLUSION: This research finding indicates that PSPY affects lipid metabolism and has a potential protective effect of reducing systemic inflammation and oxidative stress.KEYWORDS: anthocyanin, high-fat diet, lee index, lipid metabolism, oxidative stress, purple sweet potato yogurt, systemic inflammation